2019
DOI: 10.33314/jnhrc.v17i01.1357
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Bilateral Simultaneous Percutaneous Nephrolithotomy

Abstract: Background: To evaluate the safety and efficacy of bilateral simultaneous percutaneous nephrolithotomy in one tertiary hospital in Nepal.Methods: Retrospective study was done for all patients that underwent bilateral simultaneous percutaneous nephrolithotomy in our center from January 2010 to December 2017. The study included 36 male and 16 female patients with totalof 104renal units at an average age of 37 years (range 3 -65 years). Five patients were planned for bilateral simultaneous Percutaneous nephrolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study results show that the impact of cluster analysis study of patient care VAS score after PCNL, study results showed that after treatment, the two groups BI scores were significantly increased, SAS and pain were significantly reduced, but the changes are more obvious in research group ( P < 0.05), and the result of research and clinical findings of other scholars has higher consistency [ 20 ], and thus show that the cluster of nursing intervention should be widely applied. In the study, knowledge awareness and satisfaction change were investigated after patients were bundled nursing intervention, patients received health education, prevention, and intervention through reasonable measures, and it can improve the degree of cognitive disorders in patients [ 21 23 ]. The results showed that the study group's knowledge rate was 86.3 percent, and the control group was 96.6 percent, respectively, and that the study group's awareness of knowledge was higher ( P 0.05) than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The study results show that the impact of cluster analysis study of patient care VAS score after PCNL, study results showed that after treatment, the two groups BI scores were significantly increased, SAS and pain were significantly reduced, but the changes are more obvious in research group ( P < 0.05), and the result of research and clinical findings of other scholars has higher consistency [ 20 ], and thus show that the cluster of nursing intervention should be widely applied. In the study, knowledge awareness and satisfaction change were investigated after patients were bundled nursing intervention, patients received health education, prevention, and intervention through reasonable measures, and it can improve the degree of cognitive disorders in patients [ 21 23 ]. The results showed that the study group's knowledge rate was 86.3 percent, and the control group was 96.6 percent, respectively, and that the study group's awareness of knowledge was higher ( P 0.05) than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of persistent bleeding after operation may be the tearing of renal pelvis or calyces, perforation of mucous membranes, rupture of small renal vessels, among many others. However, the intermittent bleeding after operation may be complicated with renal arteriovenous fistula or pseudoaneurysm (14). However, none of the patients in the laser surgery group had massive postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Differently of our findings, those authors had two major complications; one patient had hydrothorax that required thoracic drainage and another required surgical evacuation of clots from the bladder. 12 Sofer et al, in a comparative study of bilateral versus unilateral PCNL, showed that sbPCNL is associated with a significantly increased postoperative creatinine level, a decreased postoperative hemoglobin level, a higher blood transfusion rate (9% versus 2%), and a longer hospital stay. 15 In our study, there was no significant difference in postoperative serum creatinine between simultaneous and staged procedures; however, we also found a higher transfusion rate and a tendency for longer hospital stays in sbPCNL.…”
Section: Discussionmentioning
confidence: 99%